2023
DOI: 10.3390/su15086844
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Digitainability: Encouraging Mindfulness to Harness the Power of Digitalization for Sustainable Development

Abstract: Digitalization is globally transforming the world with profound implications. It has enormous potential to foster progress toward sustainability. However, in its current form, digitalization also continues to enable and encourage practices with numerous unsustainable impacts affecting our environment, ingraining inequality, and degrading quality of life. There is an urgent need to identify such multifaceted impacts holistically. Impact assessment of digital interventions (DIs) leading to digitalization is esse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 193 publications
0
11
0
Order By: Relevance
“…It is imperative to provide comprehensive education to young individuals regarding all SDGs to enhance their comprehension of the fundamental principles and significance of these goals. This assertion has been previously acknowledged and emphasized by various scholars [73][74][75]. Unfortunately, recent research has indicated that the younger generation lacks adequate understanding pertaining to the SDGs.…”
Section: Discussionmentioning
confidence: 85%
“…It is imperative to provide comprehensive education to young individuals regarding all SDGs to enhance their comprehension of the fundamental principles and significance of these goals. This assertion has been previously acknowledged and emphasized by various scholars [73][74][75]. Unfortunately, recent research has indicated that the younger generation lacks adequate understanding pertaining to the SDGs.…”
Section: Discussionmentioning
confidence: 85%
“…Digital technologies and their connected innovations help to more efficiently control and reduce air and water pollution [14]. Digitalization helps us to achieve more efficient energy use in many fields, such as waste processing, optimization of supply chains, production, logistics, and economy of residences, which in turn reduces CO 2 emissions [14,18,20].…”
Section: Digitainabilitymentioning
confidence: 99%
“…Furthermore, numerous studies have examined the negative effects of digitalization on specific areas. However, it is not possible to infer the overall impact of digital transformation on the sustainability of business operations solely from these focused studies [20]. To understand the general impact of digital transformation on achieving sustainability goals, more generalizable studies are required.…”
Section: Digitainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to advanced technologies, such as industrial big data, modes of production are transitioning toward ecological and collaborative approaches and increasing supply chain connectivity [1]; these approaches and connectivity optimize the standards for shared resources, reduce digital resource waste in data management, and achieve overall sustainability in production [2]. This transformation has profoundly affected the forms of cooperation between enterprises and the way they maintain competitiveness [3], shifting from order-driven to value-driven business cooperation.…”
Section: Introductionmentioning
confidence: 99%